Rapidly Progressive Pituitary Apoplexy in a Patient with COVID-19 Disease Treated with Endoscopic Endonasal Surgery - Taneja, Charit; Fazeli, Pouneh K.; Gardner, Paul A.; Wang, Eric W.; Snyderman, Carl H.; Mahmud, Hussain (Journal of Neurological Surgery Reports, 2022)
This report describes a case of pituitary apoplexy with rapidly evolving hemorrhage in a 74-year-old female with coronavirus disease 2019 (COVID-19) disease. The patient presented with severe headache and mild respiratory symptoms, with laboratories concerning for pituitary hypofunction. Brain imaging demonstrated a sellar mass concerning for a pituitary adenoma with ischemic apoplexy. She subsequently developed visual deficits within 24 hours of presentation, and repeat imaging demonstrated evolving hemorrhage and new mass effect on the optic chiasm. She was successfully managed with urgent endoscopic endonasal surgery despite her COVID-19 positive status by taking special intraoperative precautions to mitigate SARS-CoV2 transmission risk. Only a handful of cases of pituitary apoplexy have been reported in association with COVID-19 disease, and even fewer reports exist of endonasal procedures in such cases. We discuss the potential implication of COVID-19 in the occurrence of pituitary apoplexy, in addition to the safety and success of endonasal surgery in this population.
Keywords: pituitary apoplexy; COVID-19; endonasal surgery